Scenario Approach to the Development and Use of Learning Management System in Universities - Martyushova, Y.G. (Psihologičeskaâ nauka i obrazovanie, 2017)
The article offers a scenario approach to the design of learning management system (LMS) structure. It is argued that the LMS structure and it functional components depend on the scenarios of its use in educational process which, in turn, are determined by the type of subject that is based on the main component of education content. There are three categories of the LMS users in the educational process in university: students, teachers, and administrators, and their roles differ from each other. The article provides detailed scenarios of how the LMS is used by various categories of users and describes the structure of the LMS in relation to these scenarios. On the one hand, the LMS represents a structured base of content: that is, it contains theoretical materials as well as tasks and exercises along with certain scales that reflect their difficulty. The weight of these tasks, initially determined by experts, can then be automatically corrected using the methods of mathematical statistics. On the other hand, implementing the described scenarios requires an electronic operating cover of the LMS, among the functions of which is the organization of control and self-checking, as well as providing storage and processing statistics of the LMS use. These statistics should then be automatically turned into the current rating of users which is important for knowledge evaluation and support of learning motivation in students during a semester. Предлагается сценарный подход к построению структуры электронного учебника. Высказывается предположение о зависимости структуры учебника, состава входящих в него функциональных компонентов от сценариев его использования в учебном процессе, которые обусловлены типом учебного предмета, определенным по ведущему компоненту содержания образования. В учебном процессе, проходящем в университете, выделяются три категории пользователей электронных учебников: студент, преподаватель, администратор, роли которых различны. Подробно рассматриваются сценарии использования электронного учебника различными категориями пользователей, описывается структура электронного учебника, соответствующая приведенным сценариям. Обращается внимание на то, что, с одной стороны, электронный учебник представляется как структурированная база контента, т.е. теоретического материала, а также задач и упражнений, наделенных соответствующими весами, отражающими их сложность. Веса, изначально определенные экспертами, затем могут автоматически корректироваться с использованием методов математической статистики. С другой стороны, понятно, что для реализации предложенных сценариев необходима электронная управляющая оболочка учебника, к функциям которой относится организация контроля и самоконтроля, обеспечение хранения и обработки статистики использования электронного учебника контингентом пользователей. Утверждается, что на основе этой статистики должно быть, в частности, предусмотрено автоматическое формирование текущего рейтинга пользователей, что является важным аспектом при принятии решения по оцениванию знаний студентов при рейтинговой форме контроля по предмету и создании мотивации в течение семестра.